MONTMORILLONITE APPLICATION IN ELECTROCHEMICAL TREATMENT EFFLUENT - Zárate A., Gisela (2006)
In this work it is proposed the usage of montmorillonile for zinc and copper ion removal from electrochemicai effluents. The initial concentrations of zinc etfluents analyzed in this work, varied between 1O and 94 ppm in Zn2+, being the pH between values 6-7. The obtained percentage of removal with calcic and sodic montmorillonite surpassed in all the cases 98%. The initial concenlrations of copper effluents oscillated between 16 and 160 ppm. in Cu2•. In the treatment of these effluents with calcic montmorillonite an elimination between 98.5 and 85.5% was reached al pH values between 4-5. In both cases it was used a relation of 5 grams ot clay 1200 milliliters of effluent for one hour agitation .